THE DESCRIPTION OF ANXIETY SCORES IN POSTPARTUM MOTHERS DURING THE BREASTFEEDING PROCESS AFTER BEING EDUCATED WITH VIDEO AND MATERNAL AND CHILD HEALTH BOOK (MCH) - Putriastuti, Widya; Febriani, Susanti; Nurlina, Entang Lina (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Anxiety is a common issue experienced by postpartum mothers, and it can interfere with the lactation process. During the postpartum adaptation period, many mothers face psychological challenges, including heightened anxiety. This emotional state can disrupt the hormonal regulation of prolactin and oxytocin—two key hormones responsible for breast milk production—thereby slowing the milk release and making breastfeeding more difficult. A preliminary observation conducted at Independent Midwifery Practice (IMP) Purwanti involving five postpartum mothers found that three mothers who experienced mild anxiety had delayed milk production, while the two mothers without anxiety had faster milk flow. This study aimed to assess changes in anxiety levels among postpartum mothers after receiving breastfeeding education through two different methods: animated videos and the Maternal and Child Health (MCH) book. The descriptive-analytic study was conducted from February to April 2023, involving all postpartum mothers on day five at IMP Purwanti, totaling 32 participants. The participants were divided equally into two intervention groups. Group one received health education via animated videos, while group two received education through the MCH book, with 16 mothers in each group. The results showed that in the animated video group, all 16 mothers (100.0%) reported no anxiety after the intervention. In the MCH book group, 15 mothers (93.8%) reported no anxiety, and only 1 mother (6.3%) experienced mild anxiety. None experienced severe anxiety. These findings suggest that both animated videos and MCH books are effective educational tools for reducing postpartum anxiety. Health services should consider integrating innovative educational strategies into routine postpartum care. Keywords: Postpartum anxiety, Breastfeeding education video, Maternal and child health book